Muggles, and quidditch, and squibs, oh my! A study of names and onomastic wordplay in translation, with a focus on the Harry Potter series - McDonough, Julie (University of Ottawa (Canada), 2004)
The goal of this thesis is to study names in the Harry Potter series and its French and Spanish translations. It therefore opens with an analysis of the names, nicknames, and titles that are found in the English series before elaborating on the characteristics that distinguish names with special significance from those without. The second chapter offers an analysis of the onomastic wordplay that can be found in the five English-language novels. Over the course of the third chapter, the reader will find (a) summaries of several translation theories, with a focus on those that pertain directly to the translation of names and onomastic wordplay, (b) a study of the strategies available to translators who are faced with loaded names, and finally, (c) an analysis of which of these strategies would seem to be the most useful in the translation of the Harry Potter series. Last, the reader will find the author's commentary on the treatment of names by Francois Menard, the French translator, by Alicia Dellepiane, who translated Harry Potter and the Philosopher's Stone into Spanish, and by Adolfo Munoz Garcia and Nieves Martin Azofra, who translated the remaining four volumes into Spanish. (Abstract shortened by UMI.)
Keywords: Literature, Modern.